PENGARUH DAMPAK SOSIAL DAN KELAYAKAN SOSIAL TERHADAP KETERIKATAN KERJA DENGAN KOMITMEN AFEKTIF SEBAGAI VARIABEL MEDIASI (STUDI PADA PERAWAT RUMAH SAKIT UMUM DAERAH MEURAXA KOTA BANDA ACEH) - Erni Yunita, Megawati (Departemen Manajemen, 2018)
This study aims to determine the effect of social impact and social worth to work engagement with affective commitment as a mediation variable. The empirical study conducted on nurses of RSUD Meuraxa Kota Banda Aceh using squestionnaire as a research instrument, which samples in this study is 110 people who are permanent nurses at the hospital. Probability sampling is used as a sampling technique with Simple Random Sampling method. The HLM (Hierarchical Linear Models) method is used as a data analysis method using the IBM SPSS 20 software. The results of this study indicate that social impact, social worth, and affective commitment have a positive and significant effect on work engagement. Social impact and social worth has a positive and significant impact on affective commitment, and in addition to the result that affective commitment mediates partially the impact of social impact and social worth on work engagement.Keywords : Social Impact, social worth, affective commitment, and work engagement.